2021
DOI: 10.1002/jmv.27285
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of viral variants in remdesivir‐treated and untreated SARS‐CoV‐2‐infected pediatrics patients

Abstract: Detailed information on intrahost viral evolution in SARS‐CoV‐2 with and without treatment is limited. Sequential viral loads and deep sequencing of SARS‐CoV‐2 from the upper respiratory tract of nine hospitalized children, three of whom were treated with remdesivir, revealed that remdesivir treatment suppressed viral load in one patient but not in a second infected with an identical strain without any evidence of drug resistance found. Reduced levels of subgenomic RNA during treatment of the second patient, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Accordingly, remdesivir has been postulated to increase the rate of immune escape mutations ( Colson et al, 2021 ). Furthermore, remdesivir has poor penetration in lungs ( Wang and Chen, 2020 ), and could facilitate emergence of compartmentalized resistance ( Boshier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, remdesivir has been postulated to increase the rate of immune escape mutations ( Colson et al, 2021 ). Furthermore, remdesivir has poor penetration in lungs ( Wang and Chen, 2020 ), and could facilitate emergence of compartmentalized resistance ( Boshier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing coronavirus disease 2019 (COVID-19) [ 1 ] pandemic [ 2 ] is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a sarbecovirus of the pisoniviricete order Nidovirales [ 3 , 4 ]. Since the beginning of the pandemic in late 2019 [ 5 , 6 ], SARS-CoV-2 has evolved into numerous distinct lineages, including variants of concern with varying levels of transmission, immune evasion, and disease severity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…When detecting the SARS-CoV-2 gN target, assays cannot distinguish an actively replicating virus from the input viral load; however, RT-qPCR detection of subgenomic E ( sgE ) differentiates an actively replicating virus from the viral RNA load [ 32 ]. Furthermore, fewer sgRNAs were found in COVID-19 patients and SARS-CoV-2-exposed animals after treatment with antivirals, suggesting that sgRNA concentration may help track the success of the therapeutic intervention [ 1 , 32 ]. On the contrary, some studies reported high correlation and similar trends between genomic and subgenomic RNA copy numbers longitudinally in post-exposure clinical samples, indicating a limited additional benefit of detecting sgRNA [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Remdesivir efficacy in reducing both SARS-CoV-2 viral RNA and subgenomic RNA has been demonstrated both in vitro and in vivo [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%